Использование технологии развития критического мышления при обучении русскому языку (SCIENCE and SOCIETY, 2024)
The article is devoted to the problem of using technology for the development of critical thinking in teaching the Russian language. The technology of critical thinking involves the development of skills to analyze the content, style, language form, highlight individual elements in the text, generalize, compare, combine and contrast facts, draw reasonable conclusions, and evaluate critically.